The Importance of Sociolinguistics in Foreign Language Education: A Review of Selected Paper - Nasution, Jimmy Saputra; Rahmadeny, Muhammad; Jazzawi, Ichsan (Universitas Malikussaleh, 2019)
This article aims to provide a brief description and review of the research conducted by Yasemin Bayyurt entitled